Collaborative Study of Cassava in Africa (COSCA); project description: COSCA working paper, No. 1 - Nweke, F.I. (1988)
COSCA was initiated through the realization that the potentials of cassava depends on availability of more detailed and reliable information on the cassava crop. The general objective of COSCA is therefore to improve the relevance and impact of agricultural research on cassava by International Agricultural Research Centres and National Agricultural Research Systems in Africa in order to take full advantage of. the potentials of cassava in increasing food production and incomes of poor people. COSCA will be conducted in Cote d'lvoire, Ghana, Nigeria, Zaire, Uganda and Tanzania. The major consideration in the choice of these countries is that they provide a wide range of conditions of climate, altitude, population density, and market access infrastructure in the important cassava zones of the continent in order to collect relevant information over a wide range of ecologies in the cassava belt of Africa. A systems approach, with a multi-disciplinary team, is adopted in COSCA to study cassava within the context of mixed farming and food systems. Not only will information be collected on production, processing, marketing and consumption of cassava, but also similar information will be collected on other crops which are grown or consumed in the same farming and food systems. COSCA study will be conducted in three phases, Phase I will involve broad characterization of the cassava producing zones. Information will be collected by group interviews at the village level and by key informant interviews at institutional level. Phase 1\ will involve characterization of individual production, processing, marketing and consumption units. The information will be collected on single visits and collection methods will include direct observations, field measurements, and individualized interviews. Phase III is an extension of Phase II but involves more intensive surveys with repeated interview visits for collection of information on seasonal variables. The components of COSCA are integrated into one study for data collection and analyses. Integration is assured at data collection stage through the sampling process. Phase II survey will be conducted on a subsample of Phase I sites and Phase III survey win be conducted on subsamples of Phase II. During the analyses, COSCA study is further integrated since each hypothesis will be tested with information collected at different phases and on different components. The time frame is 4 years between 1988 and, 1992, with intermediate outputs issued at the end of each phase. These outputs will be disseminated through a working paper series, research reports, journal articles, books and conference proceedings, especially the triennial symposia of the African Branch of the International Society of Tropical Root Crops.